Implementation Of The E-Kinerja Application Program In Assessment Of Attitude In Employee Performance System At The Regional Service Agency Of Gorontalo Regency Office - Srihandayani Suprapto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research aims to determine the extent of the implementation of the E-performance Application Program in Attitude Assessment in the Performance System of Civil Servants at the Regional Personnel Agency Office of Gorontalo Regency. Attitude assessment on the employee performance system is something that must be carried out in an agency or company, this is done to find out whether the results of employee performance are increasing or decreasing. This type of research uses a qualitative research approach with a descriptive research approach. The results based on research findings that the application of the E-performance Application Program in Attitude Assessment on the Employee Performance System at the Gorontalo Regional Personnel Agency Office was quite good, this can be seen from the consistency of employees in serving civil servants in accordance with existing procedures although they still have some problems, but does not become a barrier in the attitude assessment process on the employee performance system